Developing the complex antioxidant from walnut leafs and calendula extracts - Білоус, Олеся Валеріївна; Демидов, Ігор Миколайович; Бухкало, Світлана Іванівна (Eastern-European Journal of Enterprise Technologies, 2015)
This article is devoted to research the oils and fats oxidation processes. The methods of protection oils, fats and fat-containing products from oxidative damage are given. The most attention is paid to products protection from oxidation with the help of inhibitors. Natural antioxidants from plant material are reviewed. Complex antioxidant based on walnut leaves and calendula extracts are developed and investigated. The ability of the developed oxidation inhibitor to inhibit the oxidation of sunflower oil is demonstrated. The antioxidant feature was estimated from the values of induction periods. By adding an extract of the walnut leaves in amount of 0,025 % (counting dry substance) and calendula extract in amount of 0,025 % (counting dry matter) into sunflower oil, the induction period is doubled. The synergy between sunflower oil tocopherols and antioxidants based on walnut leaves extracts and calendula extract was found. Thus, the complex herbal antioxidant that can increase the stability of sunflower oil to oxidation is developed.